KEPUTUSAN ETIS DALAM PERSPEKTIF IDEOLOGI ETIS - Dewi Monalisa Putri (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study investigates the influence of ethical ideologies on ethical judgment which is divided into legal and illegal situations, case study for future accountants in Batam. The questionnaire survey using 264 respondents that comprises Ethics Position Questionnaire (EPQ) and ethical dilemma vignettes. Taxonomy of ethical ideologies driven by two factors: idealism and relativism, also taxonomy of ethical ideologies divided into four categories: exceptionist, subjectivist, absolutist and situationist. In achieving the objectives, multiple linear regression and MANOVA were performed. The results showed ethical ideologies have significant impact on ethical judgment. The study found significant positive and negative impact of idealism and relativism, respectively, on ethical judgment. Absolutist is stricter in making ethical judgment for both situations of legal and illegal. Subjectivist is more lenient in making ethical judgment for legal situations, but situationist is more lenient in making ethical judgment for illegal situations